Accurate calculation of the slip factor of axial cascades and impellers for arbitrary blade shapes - Smith, Henrik; Semel, Matthias; Epple, Philipp; Bleiziffer, Mihai; Delgado, Antonio (Proceedings of the ASME Turbo Expo, 2011)
Nowadays, design, redraft and optimisation strategies of axial fans often still rely on the one dimensional mean line theory. However, as it is well known, it is based on a number of assumptions that do not apply to real flow behaviour so that various deviations can be observed. In the present paper, the plane potential theory is used to examine and calculate these deviations. The behaviour of axial cascades is analysed in general and a slip factor is computed. On this basis a quasi-3D calculation method is developed. It is applied to an exemplary impeller and the results are compared with 3D CFD computations. The main characteristic figures are presented and different angle correction and angle exaggeration methods are investigated and compared. Finally, the applicability of the presented method to a precise axial fan design process is illustrated. Copyright © 2011 by ASME.
UnivIS-Import:2017-01-09:Pub.2011.tech.ITC.stmmec.accura

Application of an inverse cascade analytical and numerical design method used in the design of axial fans - Bleiziffer, Mihai; Epple, Philipp; Smith, Henrik; Semel, Matthias; Delgado, Antonio (Proceedings of the ASME Turbo Expo, 2011)
This contribution presents an inverse design method for axial flow fans validated by 3-D RANS numerical simulations. It is based on an analytical performance derivation for different free-vortex distributions combined with a mean-line pre-design tool and supported by a new 2-D cascade potential flow computational method. This computes the 2-D planar cascade flow field and the inviscid deflection angle of thin arbitrary shape airfoils at different machine radii followed by a numerical radial integration into a quasi-3-D method. For validation, several fan designs were investigated, showing the influence of important design parameters as well as the potential of the present method by redrafting an industrial fan. The 2-D planar potential cascade code was validated against the Weinig's coefficient diagram for flat plate and circular arc cascades. Copyright © 2011 by ASME.
UnivIS-Import:2017-01-09:Pub.2011.tech.ITC.stmmec.applic

Calculation of the flow field in an axial fan with variable swirl distribution at off-design operating points - Delgado, Antonio; Semel, Matthias; Vogel, P. (International Conference on Fan Noise, Technology and Numerical Methods, FAN 2015, 2015)

CFD computation, analysis and design of a two-bladed wastewater pump - Litfin, Oliver; Mohr, Christian; Haddad, Kais; Epple, Philipp; Semel, Matthias; Becker, Klaus; Klein, Horst; Delgado, Antonio (ASME 2011 International Mechanical Engineering Congress and Exposition (IMECE 2011), 2011)
In this work a wastewater pump with a two-bladed prototype impeller and a specific speed of 0.68, referring to a wellestablished industrial design, was simulated in a commercial CFD solver, ANSYS CFX. Simulations of the impeller only and of the complete pump with spiral casing including a detailed analysis of the flow patterns were performed. A parameter study with around 25 new designs containing variations of the inlet angle and the wrap angle was carried out, leading to significant improvements of the flow pattern as well as of the hydraulic efficiency. Based on the optimum leading edge and wrap angle, the total head was improved by variation of the exit blade angle. Having set the better main dimensions, the effect of the blade shape, i.e. blade angle distribution, was investigated. Here it is shown that changing the blade angle distribution in such a way that the point of maximum blade angle is shifted to a bigger radius can lead to substantial improvements. One special focus in this whole study was also to describe and control the behavior of the relative eddy, which is directly related also to the slip factor. In the scope of this work it is shown how it is possible to influence and move the relative eddy to the best position, since due to the small relative velocities in the blade passage it is impossible to fully avoid it. A detailed analysis of these CFD results is presented as well as the recommendations for an efficient design of this special type of wastewater pump impellers. Copyright © 2011 by ASME.
UnivIS-Import:2017-11-07:Pub.2011.tech.ITC.stmmec.cfdcom

Compact test rig design for fans and blowers - Epple, Philipp; Semel, Matthias; Grashof, Bettina; Delgado, Antonio (Proceedings of ASME International Mechanical Engineering Congress and Exposition, 2014)
In order to develop high efficiency fans and blowers the design methods are being improved continuously. The same is valid for the modern CFD (Computational Fluid Dynamics) programs, which are used in the design process in order to validate the designs. However, at the end of the development process measurements at test rigs are needed in order to verify the final design. CFD is substituting to some extend EFD (Experimental Fluid Dynamics), but still EFD is the final way to evaluate a design. Usually the universities and the industry have some test rig where measurements are done. These test rigs in general are unique and built according to a corresponding standard. However, these standards, as for example the German DIN 24 163 [1] or the European DIN EN ISO 5801 [2] prescribe only the main proportions of such test rigs while several important features are not described in detail. In particular the aerodynamic theory behind the standard is very often omitted. For example, the measurement of the pressure characteristic of a fan is performed at a pressure tab at the test chamber wall and not at the fan itself. How to assure that the pressure measured at the wall tab corresponds to the fan pressure? In this work the relevant theory behind the design of test rigs was worked out in detail for the relevant test rig features where the standards do not explain the fluid mechanical aspects. On this basis pressure and suction side test rigs were designed and completely simulated with a commercial CFD program, Ansys CFX. The goal was to develop compact test rigs according to the European DIN EN ISO 5801 [2] standard. It is shown in this work how the size of the test chamber influences the measuring results. Furthermore an in detail CFD study of a series of flow measurement devices, as inlet and Venturi nozzles, was performed. In such a way it was possible to show the influence of the dimensions of these devices on the accuracy of the measurements. Finally two test rigs were built, one for suction side and the other one for pressure side measurements. Compared to other test rigs in this category in use in the industry in Germany it was possible to reduce the size of these test rigs by a factor of about two complying with the measurement uncertainty of the DIN EN ISO 5801 standard.
UnivIS-Import:2015-07-08:Pub.2014.tech.ITC.stmmec.compac

Design study of a pyrolysis plant compressor with heavy wall erosion from metal particle impact - Omri, Riadh; Semel, Matthias; Delgado, Antonio; Rußwurm, Hans (Proceedings of the ASME 2017 Fluids Engineering Division Summer Meeting. Volume 1A, Symposia: Keynotes; Advances in Numerical Modeling for Turbomachinery Flow Optimization; Fluid Machinery; Industrial and Environmental Applications of Fluid Mechanics, 2017)
In a pyrolysis plant, a mounted centrifugal compressor takes heavy damage because of erosion originating from metal particle mixed with the inlet air flow impacting its blades and volute walls. In a first step, the original impeller design as well as other centrifugal compressor designs are studied to identify the design parameters which influence the erosion distribution, shape and magnitude. It has been concluded that the first impact plays an important role in defining the particles trajectories and the erosion on the walls. A novel impeller design method based on particle trajectories after a controlled first impact is introduced. The new setup is simulated via CFD coupled with Finnie erosion model to assess the damage. This design is improved in a further step. Adequate simulation setups such as interfaces, boundary conditions and particle coupling methods with carrier fluid are introduced. This study focuses on predicting the particle trajectory within the impeller to reduce the impacts on blade walls and thus reducing the erosion rate. For all designs, the analysis is conducted in the same stage operating point, this point is defined at a predefined volume flow VF [kg/m3] and total-to-static pressure Δp[Pa] as is recommended for the pyrolysis facility including the compressor. Simulations are conducted in a steady state with compressible air at high static temperature going to 530°C. For CFD calculations the software in use is CFX of the ANSYS Group. All mesh used is structured and produced by TurboGrid for the blade rows and with Icem for inlet, outlet and volute. The final compressor design contain the design recommendation for hub form and outlet flow angle.

Extended mean line theory for axial fans - Analytic calculation of the flow characteristics for off-design points - Semel, Matthias; Epple, Philipp; Bleiziffer, Mihai; Delgado, Antonio; Smith, Henrik (Proceedings of the ASME Turbo Expo, 2011)
The use of axial fans is very common for industrial applications. The most common design case is the free vortex design. It ensures constant meridional velocity and hence an axisymmetric and two-dimensional flow. Those designs have proved to be robust and to deliver good results. However, the free vortex model holds only at the design point. At off-design points the flow characteristics differ substantially from the free vortex model, whereby the extent of validity of a forced vortex model is obtained. Solving the equation of radial equilibrium for off-design points enables a more precise design prediction considering the impact of the variable meridional velocity and the angular momentum. This approach can be applied to free vortex models as well as forced vortex models. In the present work theoretical formulas for the flow characteristics at off-design points were developed and implemented. Three angular momentum profiles, one free vortex and two forced vortex models, were analyzed relative to the change in the meridional velocity and angular momentum profiles. The impact of these modifications on the performance characteristics of axial fans, such as pressure, efficiency, torque and hydraulic power was investigated. Comparing design prediction with numerical CFD validation leads to a precise and extensive analysis. The validity of the used approach is demonstrated. Thus a qualitative prediction of flow characteristics for any axial-impeller at off-design is obtained.This allows for a in depth understanding of the fundamental working principles and consequences of the radial equilibrium equation at the design and also at off design points. Copyright © 2011 by ASME.
UnivIS-Import:2017-01-09:Pub.2011.tech.ITC.stmmec.extend

On the preliminary design of axial fans: extending the validity of the flow assumptions over the whole hydraulic characteristic and improvement of modeling - Semel, Matthias; Grashof, Bettina; Grilliat, Julien; Delgado, Antonio (Proceedings in Applied Mathematics and Mechanics, 2014)
UnivIS-Import:2015-07-08:Pub.2014.tech.ITC.stmmec.onthep

Prediction of the flow characteristics of an axial fan at off design - Semel, Matthias; Epple, Philipp; Litfin, Oliver; Grashof, Bettina; Delgado, Antonio (Proceedings of the Conference on Modelling Fluid Flow, 2012)
UnivIS-Import:2015-04-16:Pub.2012.tech.ITC.stmmec.predic_3

Preliminary design of axial fans at off-design-working points - Semel, Matthias; Grilliat, Julien; Delgado, Antonio (Proceedings of the ASME Turbo Expo, 2014)
An analytical formulation for axial fan performances at and off design point is proposed for an arbitrary work distribution. It is shown that the total pressure, total-to-static pressure and hydraulic efficiency characteristics can be described by means of hyperbola, straight lines and parabola. This formulation is applied to axial fans with free vortex work distributions, allowing a theoretical study onto the influence of the hub-to-tip ratio. Theoretical predictions are compared with numerical simulations. Good qualitative agreements are found. Conclusions onto the best practice guidelines for the design of axial fan according to a free vortex work distributions are presented.
UnivIS-Import:2018-02-22:Pub.2014.tech.ITC.stmmec.prelim

Radial impeller design optimization matched for high efficiency fans - Epple, Philipp; Semel, Matthias; Smith, Henrik; Litfin, Oliver; Delgado, Antonio (ASME 2011 International Mechanical Engineering Congress and Exposition (IMECE 2011), 2011)
Radial fans and blowers are widely used in many different fields, such as heater blowers or fans and blowers for vacuum cleaners. Although the impellers for these fans are already quite well optimized, it is possible to increase the efficiency of the fan matching the impeller properly to it. A very common fan optimization strategy is to increase the efficiency of the radial impeller, keeping its operating point, i.e. the flow rate of maximum efficiency. However, in most of these cases the impeller is not matched to the fan and hence this procedure will not deliver the best fan, even if the efficiency of the impeller is improved. In order to understand how an optimization of the fan has to be done, a theoretical treatment is presented. Detailed theoretical formulas are presented and discussed. In order to validate the theory, a series of well directed impellers and fans was designed, CAD models constructed and using ANSYS CFX finally the corresponding flow simulation was performed. It is shown how the impellers have to be modified in order to shift the flow rate of maximum efficiency without significant decrease in efficiency. Finally a detailed experimental study was performed at the test rig conforming the German engineering norm DIN 24 163 [1]. Here the theoretical achievements were systematically verified at the test rig for vacuum cleaner fans. It is shown how to, based on this theory, from the very beginning design the radial impellers such that they are perfectly matched to the full fan. In such a way it is shown how to increase the efficiency of radial fans and blowers substantially. Copyright © 2011 by ASME.
UnivIS-Import:2015-04-16:Pub.2011.tech.ITC.stmmec.radial
Keywords: CFD; Impeller-system matching; Radial impeller design

System matched 3D radial impeller design with variable inlet angle distributions - Semel, Matthias; Smith, Henrik; Epple, Philipp; Litfin, Oliver; Delgado, Antonio; Pfannschmidt, Klaus; Grobeis, Detlev (Proceedings of ASME Turbo Expo 2012, 2012)
In vacuum cleaners radial impellers with high rotational speed are very often used. A high rotational speed is connected with a best efficiency point of the radial impeller at a high flow rate. This is contrary to the working point of the whole system. Thus there is need for a radial impeller designs having a high efficiency at low flow rates under the restriction of a high rotational speed. One important parameter connected to the hydraulic efficiency characteristics of the radial impeller is the blade inflow angle b1. In order to shift the best efficiency point towards lower flow rates radial impellers with double curved blades and a linear b1 distribution were designed and CFD simulations were done in order to investigate the effect of this approach. A linear variation of the inflow angle b1 enables the designer to shift the efficiency characteristics of the impeller towards lower flow rates with a gain in hydraulic efficiency and pressure increase. Copyright © 2012 by ASME.
UnivIS-Import:2015-04-16:Pub.2012.tech.ITC.stmmec.system

Towards multiple operating point axial fan design - Semel, Matthias; Haag, Viktor; Delgado, Antonio; Grilliat, Julien (ASME Turbo Expo 2015: Turbine Technical Conference and Exposition, 2015)
The dimensionless performances of an axial fan are derived analytically from an arbitrary work distribution. The formulation is illustrated using five different work distributions at a selected operating point and comparing the resulting hydraulic characteristics. A first validation of the formulation is brought by means of RANS and URANS of an axial fan with free vortex work distribution. It is shown that a single RANS prediction at the design point allows predicting the hydraulic characteristic up to 20% off the design flow rate with very good accuracy. Based on these results, a strategy for axial fan design at multiple operating points is propose
UnivIS-Import:2016-06-01:Pub.2015.tech.ITC.stmmec.toward